The octagon of opportunities in obesity - Sanjay Kalra; Madhur Verma; Saurabh Arora; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
The Ominous Octet is a popular construct, which has been used to describe the aetiopathology of diabetes, as well as the endocrine causation of obesity. We utilize this model to create a smart and salutogenic rubric of obesity pathogenesis. Our optimistic Octagon of Opportunities lists eight causative or contributory factors, all of which are associated with the development of obesity. The model gives equal weightage to the biomedical and psychosocial arms of the biopsychosocial model of health. The framework encourages a proactive and comprehensive approach to the prevention and management of obesity. Continued...